Design and experiment of active obstacle avoidance control system for grapevine interplant weeding based on GNSS - Hao Zhang; Zejiang Meng; Shiwei Wen; Guangyao Liu; Guangrui Hu; Jun Chen; Shuo Zhang (Smart Agricultural Technology)
Traditional passive obstacle avoidance mechanical weeding strategies heavily relied on touch rods, which led to a high crop damage rate and low weeding efficiency during operations. This study proposed an obstacle avoidance information collection scheme that integrates precise detection of obstacle positions and coordinate conversion of weeding tool positions. An active obstacle avoidance control system based on obstacle positions and real-time tool status was designed. This system consisted of the autonomous navigation equipment, obstacle avoidance information collection units, the control system module, hydraulic execution components, and the real-time monitoring sensor. Based on the requirements for active obstacle avoidance, the study established the relationship between the obstacle avoidance information collection units, hydraulic execution components, and the real-time monitoring sensor, and determined a precise active obstacle avoidance control scheme. Field tests were conducted using machine forward speed as the test factor, with inter-row weeding coverage rate and plant damage rate as evaluation indicators. The test results indicated that when the machine forward speed was 460 mm/s, the combined effect of inter-row weeding coverage and operational efficiency was optimal, with an average inter-row weeding coverage rate of 94.62 % and a plant damage rate of 1.94 %. The active obstacle avoidance weeding scheme proposed in this study provided a technical reference for improving inter-row weeding effectiveness in orchards.